HYDROGEOLOGICAL CONDITIONS USING AN INTEGRATION OF AQUIFER GEOMETRY MODEL AND GROUNDWATER CHARACTERISTICS IN THE BANDUNG CITY AREA - Kombara, Prayoga Satyagraha; Barkah, Mochammad Nursiyam; Listiawan, Yudhi; Hadian, Mohammad Sapari Dwi (Fakultas Teknik Geologi Universitas Padjadjaran, 2026)
ABSTRACTThe rapid population and economic growth in Bandung City has driven increased groundwater use, necessitating an understanding of hydrogeological conditions to prevent negative consequences. This study aimed to identify the distribution of subsurface rocks, hydrostratigraphy, and groundwater characteristics in shallow aquifer systems through aquifer geometry modeling and ground-based observations. The model was developed by integrating regional geological data, 22 one-dimensional geophysical points, 7 well logging points, andprevious research results, and analyzed using modeling software and GIS software. Resistivity interpretation reveals aquifer lithology consisting of coarse tuff, lapilli, and tuffaceous sandstone (21–103 Ohm.m), aquiclude lithology consisting of fine tuff, tuffaceous claystone (0–30 Ohm.m), and volcanic breccia (101–350 Ohm.m), and aquifug lithology in the form of lava (>350 Ohm.m). The model shows the dominance of tuff sandstone in the northwest, fine tuff in the northeast, and tuff claystone in the southeast. The model revealed two types ofdeveloped aquifers, unconfined aquifer at a depth of 0–34.08 m (shallow aquifer system) and confined aquifer at 41.75–68.5 m (deep aquifer system). The characteristics of groundwater in the shallow aquifer system are categorized as fresh groundwater with EC values of 183–897 µS/cm, TDS 92–447 mg/l, and pH 5.4–6.86. Spatial distribution analysis of EC, TDS, and pH values is influenced by lithology, topography, and land cover. Vegetation in the upstream area preserves groundwater quality, while the dominance of built-up land and plantations increases EC, TDS, and pH to close to neutral levels. The results of this study emphasize the need for vegetation conservation in the upstream area, control of land use change, and urban spatial planning based on recharge to maintain the sustainability of groundwater resources in shallow aquifer system in the Bandung City area.Keywords: Groundwater, Hydrostratigraphy, Model, Aquifer, Groundwater Characteristic